Free DICOM de-identification tools in clinical research: functioning and safety of patient privacy. - Aryanto, K.; Oudkerk, M.; Ooijen, P.; Aryanto, K Y E; van Ooijen, P M A (European Radiology, 2015)
Purpose: To compare non-commercial DICOM toolkits for their de-identification ability in removing a patient's personal health information (PHI) from a DICOM header.Materials and Methods: Ten DICOM toolkits were selected for de-identification tests. Tests were performed by using the system's default de-identification profile and, subsequently, the tools' best adjusted settings. We aimed to eliminate fifty elements considered to contain identifying patient information. The tools were also examined for their respective methods of customization.Results: Only one tool was able to de-identify all required elements with the default setting. Not all of the toolkits provide a customizable de-identification profile. Six tools allowed changes by selecting the provided profiles, giving input through a graphical user interface (GUI) or configuration text file, or providing the appropriate command-line arguments. Using adjusted settings, four of those six toolkits were able to perform full de-identification.Conclusion: Only five tools could properly de-identify the defined DICOM elements, and in four cases, only after careful customization. Therefore, free DICOM toolkits should be used with extreme care to prevent the risk of disclosing PHI, especially when using the default configuration. In case optimal security is required, one of the five toolkits is proposed.Key Points: • Free DICOM toolkits should be carefully used to prevent patient identity disclosure. • Each DICOM tool produces its own specific outcomes from the de-identification process. • In case optimal security is required, using one DICOM toolkit is proposed.